TECHNOLOGICAL SUPPORT FOR PROTON THERAPY (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The paper reviews the main parts of proton therapy: cyclotron, beam transport system, and irradiation unit with a radiation head. Several advantages of proton therapy, which is an alternative to surgical procedures.